Barriers Access to Housing Finance by the Low-Income Groups: National Housing Finance Corporation (NHFC) in South Africa - Limba, Edwin Mandlakayise (Graduate School of Business (GSB), 2019)
South Africa (SA) has been experiencing a serious challenge in terms of addressing housing problems and one of the factors is access to finance, mainly by the lower income earners. Government programmes like Financial Linked Individual Subsidy Programme (FLISP) that work through the National Housing Finance Corporation (NHFC) to provide affordable subsidy finance for housing to households who earn in the range of R3 501 and R15 000 do not make a significant impact necessary to improve access to affordable housing finance. The NHFC has approved and disbursed few and low amounts for FLISP hence questions have been raised as to the challenges that low-income earners experience when accessing affordable housing finance through the NHFC and its role in creating human settlements that is sustainable. The objective is therefore to undertake a descriptive and exploratory study of the FLISP program to enhance understanding of the effectiveness of NHFC in provision of affordable housing financing accessibility by the low-income groups in Johannesburg. The sample of participants was drawn from the beneficiaries of loans and NHFC officials using observations, questionnaires and semi structured individual interviews. The mixed research method is adopted using both the primary and secondary to collect data from NHFC and is analysed by means of descriptive statistics such as percentages, tables and frequencies. Data analysis showed that accessibility for housing finance remains an obstacle faced by the low-income households. Convergent mixed method is adopted in the study to understand why the NHFC has been not effective in addressing housing finance for low-income groups. The study found that the major challenges that low-income earners encounter in accessing affordable housing finance range from the deposit amount required, interest rates and affordability in repayments of loans. It is recommended that there should be an enhancement in the housing policy to focus on the low-income groups, also, alternative mechanism such as provision of serviced land and partnerships between government and commercial banks may improve the current conditions.